LEGAL POLITICS IN THE GOVERNANCE OF PROVIDES AND ROUTES IN INDONESIA - Budi Priyatmono (Polteknik Ilmu Pemasyarakatan, 2018)
The management policy of Prison is still experiencing obstacles from various problems that have arisen at the end. Frequent occurrences of vulnerability, chaos and escape are part of the governance of poor prisons. This study uses descriptive normative research. There are two main issues raised are: 1. How is the legal politics in the management of correctional institutions in Indonesia? and 2. How is the management of correctional institutions in supporting the improvement of correctional performance in Indonesia? so that there are still many problems that result from errors in correctional governance. To improve the performance of prisons requires adequate facilities and infrastructure and professional officers in carrying out their duties and functions. So the conclusion is that management needs to be done that can improve prisons that have experienced cracks and their management requires involvement of various elements including facilities and infrastructure and resources adequate human.